Aerodynamics characteristics around simplified high speed train model under the effect of crosswinds - Mohd Salleh, Sufiah; Mat Ali, Mohamed Sukri; Shaikh Salim, Sheikh Ahmad Zaki; Ishak, I. A.; Shirakashi, Masataka; Muhammad, Sallehuddin (Asian Research Publishing Network (ARPN), 2017)
The aerodynamics problems of train commonly come when the flow pass through train body. The increasing speed of train to achieve highly technology demands has led to increase the forces and moments and increase sensitivity of train stability and may cause the train to overturn. In this paper, two prisms arranged in tandem represent a simplified model of high speed train are performed at different yaw angle ranging from 0˚ to 90˚ by using the unsteady ReynoldsAveraged Navier Stokes (URANS) equation combined with k-ω SST turbulence model. The Reynolds number is 3.14x105 based on height of the train and the free stream velocity. The aerodynamic quantities such as the side force, lift force and drag force coefficient show a similar trend where the forces increase with the yaw angle until a certain critical yaw angle before start to decrease till the yaw angle of 90˚. The flow structure around the train under the effect of crosswind is visualized. The vorticiticy start to form from the nose and slowly drifts away further towards the trailing edge. The two-dimensional mean streamlines on the cross-section of train at different yaw angle show that the size of vortex increase as the yaw angle increase. Time averaged pressure contour plotted on the cross section along x-axis show the variation of region between high pressure and low pressure region on the leeward and windward side of the train model that may cause train to overturn.